Normative blood pressure response to exercise stress testing in children and adolescents - Diana Zannino; Michael M H Cheung; Melanie M Clarke; Natalie P Stewart; Jonathan P Glenning; Salvador Pineda-Guevara; Jolien Kik; Jonathan P Mynard (Open Heart, 2021)
Objective To describe normative values for blood pressure (BP) response to maximal exercise in children/adolescents undergoing a treadmill stress test.Methods From a retrospective analysis of medical records, patients who had undergone a Bruce protocol exercise stress test, with (1) normal cardiovascular system and (2) a body mass index percentile rank below 95% were included for analysis. Sex, age, height, weight, resting and peak heart rate, resting and peak systolic blood pressure (SBP), test duration, stage of Bruce protocol at termination, reason for undergoing the test and reason for termination of test were collected. Percentiles for exercise-induced changes in SBP were constructed by age and height for each sex with the use of quantile regression models.Results 648 patients with a median age of 12.4 years (range 6–18 years) were included. Typical indications for stress testing were investigation of potential rhythm abnormalities, syncope/dizziness and chest pain and were deemed healthy by an overseeing cardiologist. Mean test duration was 12.6±2.2 min. Reference percentiles for change in SBP by sex, age and height are presented.Conclusion The presented reference percentiles for the change in SBP for normal children and adolescents will have utility for detecting abnormally high or low BP responses to exercise in these age groups.